Early detection of diabetic retinopathy using deep learning techniques - Gomes, Veronica Jessica; Alavee, Kazi Ahnaf; Sarda, Anirudh; Akhand, Zebel-E-Noor (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.